(untitled) (Malay Literature, 2012)
Hang Tuah is a character in the epic Hikayat Hang Tuah which has become the pride of Malay Literature. The epic, and especially the protagonist of the epic, Hang Tuah, have been much discussed. This is also the case where children’s literature is concerned, as the Hikayat Hang Tuah has attracted the attention of Malaysian authors to produce adaptations of stories from this epic. The stories linked to the character of Hang Tuah contain many elements of fantasy which makes them suitable for adaptation as children’s literature. Establishing what types of adaptations have been made of these stories forms the core of this study. Also, the acceptance of Hang Tuah as a hero of the Malays has been challenged by movements, especially in social realism. As a result, the character of Hang Jebat has become accepted as a heroic figure instead. However, whether or not social realism has influenced adaptations done for children, and whether there has been a shift in the figure of hero as a result of social realism are still unanswered questions which this study addresses. This study has found that adaptations of stories about Hang Tuah for children are mainly partial adaptations, and that the stories chosen for adaptation are especially those containing strong elements of fantasy. Illustrations are also an element in these partial adaptations. The study has found no trace of the influence of social realism in the adaptations. Hang Tuah is still depicted as a heroic figure while Hang Jebat continues to be depicted as the traitor. Keywords: children’s literature, Hang Tuah, adaptations, social realism, illustrations